Mental health nurses' attitudes toward self-harm: Curricular implications - David G. Shaw; Peter T. Sandy (AOSIS, 2016)
Background: Self-harm is an old problem but increasing in incidence. It has important consequences for the individual concerned, the health care system, and can impact the well-being of staff. Extensive prior research has adopted a quantitative approach, thereby failing to explore in detail the perspective of mental health nurses. The literature also neglects secure mental health settings. Methods: The study aimed to explore the attitudes of mental health nurses toward service users who self-harm in secure environments, and to inform mental health curriculum development. It was conducted in a large forensic mental health unit, containing medium and low secure facilities, to the west of London, UK. A qualitative multi-method approach was adopted, underpinned by interpretative phenomenological analysis. Data were obtained from mental health nurses using individual interviews and focus groups, and analysis followed a step-by-step thematic approach using interpretative phenomenological analysis. Results: Nurses' attitudes toward self-harm varied but were mainly negative, and this was usually related to limited knowledge and skills. The results of the study, framed by the Theory of Planned Behaviour, led to the development of a proposed educational model entitled 'Factors Affecting Self-Harming Behaviours' (FASH). Conclusion: The FASH Model may inform future curriculum innovation. Adopting a holistic approach to education of nurses about self-harm may assist in developing attitudes and skills to make care provision more effective in secure mental health settings.